DOMESTIKASI IDEOLOGI DALAM PENERJEMAHAN INJIL: INGGRIS-BALI - Frans I Made Brata Brata (Fakultas Sastra Universitas Negeri Malang, 2011)
The Bible’s translator expects his translation not only accurate, but also acceptable in accordance to the norms and cultural value of its reader. This study aims to describe the domesticating ideology in translation. Tu-VousTheory combined with Attitude, as part of Appraisal Theory in Systemic Functional Linguistics are used to investigate how the word should be used. Dynamic Equivalence Theory is utilized to describe the word in use in society. Descriptive qualitative approach in determining two principle orientations of translation techniques, methods, and ideologies were applied in analyzing the data. Questionnaires containing sentences with English terms of address in Luke’s Bible and their equivalents in Balinese were used to verify the data. The findings show that the domesticating ideology has a positive contribution to the quality of the translation with regard to its accuracy, acceptability, and readability.